2011
DOI: 10.1021/nl201225r
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon 3D FIONA of Individual Quantum Dots in an Aqueous Environment

Abstract: We report the first two-photon (2P) microscopy of individual quantum dots (QD) in an aqueous environment with both widefield and point-scan excitations at nanometer accuracy. Thiol-containing reductants suppress QD blinking and enable measurement of the 36 nm step size of individual Myosin V motors in vitro. We localize QDs with an accuracy of 2~3 nm in all three dimensions by using a 9×9 matrix excitation hologram and an array detector, which also increases the 3D scan imaging rate by 80-fold. With this 3D mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 25 publications
0
39
0
Order By: Relevance
“…Their technique allowed an 80-fold increase of the imaging rate. 190 Myosin V rotation around its own axis during the movement could be shown by Ohmachi et al, who developed a single-molecule fluorescence polarization technique for 3D orientation measurements. Their method allowed an orientation accuracy of 101 at 33 ms temporal resolution and revealed a myosin V rotation of 901 during each step.…”
Section: Single-particle Trackingmentioning
confidence: 99%
“…Their technique allowed an 80-fold increase of the imaging rate. 190 Myosin V rotation around its own axis during the movement could be shown by Ohmachi et al, who developed a single-molecule fluorescence polarization technique for 3D orientation measurements. Their method allowed an orientation accuracy of 101 at 33 ms temporal resolution and revealed a myosin V rotation of 901 during each step.…”
Section: Single-particle Trackingmentioning
confidence: 99%
“…15). 254 2PE FIONA was first validated by tracking the steps of individual QD 655 -labeled myosin V motors on F-actin with nanometer accuracy (step size, 35.8 6 6.3 nm for 2PE and 35.4 6 7.0 nm for 1PE). Impressively, widefield illumination at 785 nm was used for the 2PE tracking and was uniquely enabled by the efficient 2PE of QDs.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…The 2PE-FIONA technique provided a five-fold enhancement in S/N compared with imaging with 1PE total internal reflection microscopy. 254 Another useful application for QDs in 2PE microscopy is in vivo imaging. Larson et al demonstrated in vivo 2PE imaging of mouse vasculature (i.e., angiography) in skin and adipose tissue by injection of amphiphilic polymercoated CdSe/ZnS QD 550 and 2PE at 880 nm.…”
Section: Bioanalysis and Bioimaging With Quantum Dotsmentioning
confidence: 99%
“…These properties make the Lipo-UCNP an excellent probe for single molecule imaging. [11] Furthermore, the Lipo-UCNPs showed long-term stability in water and resistance to aggregation over an extended period of several months (Figure S4).…”
mentioning
confidence: 99%